Sistem Pemantauan Tegangan Listrik Menggunakan Mikrokontroler AT Mega 328 Berbasis Web - Kurniawan, Rudi; Wijaya, Harma Oktafia Lingga; Nugroho, Aditya (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2019)
Electricity is the source of the needs of people all over the world with electricity all human work will be easy, the main thing is electricity is a source of lighting without electricity, so there will not be an era and technology, but the use of electricity by many people who do not care about the electricity impact is a lot short circuit and fire because many electricity users do not know the current of electric current in their homes. Thus the author makes a tool that can measure the voltage used. Tools made using ACS712 and Arduino Uno sensors and Ethernet shield. The sensor will read the power supply voltage and then process it to Arduino Uno and Ethernet shield. After processing via Arduino, the ACS712 sensor readings will be displayed on the web page.